Kishida’s Maritime Turn: Japan’s Defensive Defense and Gray-Zone Balancing in the East China Sea - Aspin Nur Arifin Rivai; Dian Putri Pratiwi (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2026)
Japan’s postwar defensive orientation has been recast into a more active maritime strategy under Prime Minister Fumio Kishida. Existing studies have traced Japan’s broader security normalization, alliance strengthening, and legal-institutional change, yet they have given less sustained attention to the maritime operational logic through which those shifts were translated into balancing in the East China Sea. This article examines how Japan’s maritime defense policy evolved in response to persistent Chinese gray-zone coercion around the Senkaku Islands. Using a qualitative single-case design, it draws on Japanese strategic documents, defense reports, maritime-security data, and relevant academic literature. The analysis combines William D. Coplin’s decision-making framework with Ariel González Levaggi’s maritime-strategy typology. The article finds that Japan’s policy shift was driven by the interaction of three variables, external pressure from China, growing domestic acceptance of defense strengthening, and the fiscal-technological capacity to implement strategic change. These conditions produced a layered defensive-defense posture expressed through coastal defense, sea denial, selective sea control, and limited regional power projection. Kishida inherited an earlier trajectory of reform, then accelerated its maritime consolidation and anchored it in an East China Sea strategy suited to prolonged gray-zone competition under constitutional restraint.